Does the Consumer Protection Act 68 of 2008 provide adequate protection to the consumer with regard to unfair or unconscionable commercial practices? - Barnard, Jacolien (University of Pretoria, 2019)
Mini Dissertation (LLM)--University of Pretoria, 2018.